Understanding Sustainability Through Socio-Ecological Trade-Offs: Field Evidence of Traditional Oil Mining and Groundwater Quality Toward the SDGs - Ifan Deffinika; Alfi Sahrina; Dicky Arinta; Inanditya Widayana Putri; Adelisa Rizki Zaharani; Novi Silvia (Jurnal Penelitian Pendidikan IPA, 2026)
This study explores human-nature relationships through a socio-ecological perspective, focusing on traditional oil mining in Wonocolo, Indonesia, widely known as “Little Texas”. The analysis was conducted through field observations, in-depth interviews with 40 local stakeholders, and laboratory analysis of 40 groundwater samples collected from community dug wells. Results show residents rely on dug wells, piped-water, and artesian springs, with significant seasonal scarcity. Water quality assessment indicates that most physical parameters remain within acceptable limits (pH 6.40–8.00; electrical conductivity 0.43–2.26 mS/cm; temperature 22.00–31.00 °C). However, localized elevations in electrical conductivity at several sampling points suggest potential hydrochemical alterations in the shallow aquifer that may be associated with traditional oil extraction activities, particularly in a karst-dominated landscape. Although direct measurements of TPH and Oil & Grease were not available for a comprehensive ecotoxicological assessment, these findings highlight a critical socio-ecological trade-off in which short-term economic benefits from oil production may increasingly pressure long-term groundwater security. The study concludes that managing these interdependencies requires participatory governance and waste-stream regulation tailored to the karst landscape. Integrated policies are essential to ensure that economic benefits do not undermine the community's fundamental access to clean water, aligning with SDG 6 and SDG 12.